KOREKSI LOKASI HIPOSENTRUM GEMPABUMI DI SULAWESI UTARA MENGGUNAKAN METODE MODIFIED JOINT HYPOCENTER DETERMINATION - Sike Suwuh; Armstrong Sompotan; Sixtus Umboh (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2020)
North Sulawesi is one of the areas that has had a fairly high level of seismic activity that has occurred, due to the position of North Sulawesi Island which is located close to the earthquake source. One of the parameters of an earthquake that can be calculated is the earthquake hypocenter.Determining the hypocenter of an earthquake is very important in the world of seismology. The Modified Joint Hypocenter Determination (MJHD) method was carried out for relocation of the earthquake hypocenter. To find out how the results of the Hypocentrum Location Correction using MJHD and the tectonic pattern of the Sulawesi Sea Plate subduction zone. . The results of relocation using the MJHD (Moodifide Joint Hysopcentrum) method showed better and more accurate data quality seen from the residual value (RMS) before (≥1 s) and after relocation (≤1 S). Based on the seimicity results of relocation using the MJHD method, it was found that the earthquake clusters were concentrated at a shallow depth of the range of 20 - 80 km. At a depth of 250 - 300 and a distance of 400 km, there is a seimic gap so that earthquakes rarely occur in this zone.